MANAJEMEN STRATEGI PEMASARAN PENDIDIKAN BERBASIS MEDIA SOSIAL PADA PONDOK PESANTREN MODERN TAHFIDZUL QUR’AN MUHAMMADIYAH BOARDING SCHOOL (MBS) AT TANWIR MAMUJU - Ray Akbar Ramadhan; Herman Jelatu (Jurnal Humaniora & Sosial Sains, 2024)
This study aims to determine (1) How is the management of social media-based educational marketing strategies at the modern Islamic boarding school for memorizing the Qur'an, Muhammadiyah boarding school (MBS) At-Tanwir Mamuju, (2) Can the management of social media-based educational marketing strategies that are implemented increase students at the modern Islamic boarding school for memorizing the Qur'an, Muhammadiyah boarding school (MBS) At-Tanwir Mamuju. This study uses a qualitative approach. The analysis technique in this study uses interactive analysis techniques, namely data collection, data presentation, reduction and conclusions to determine the management of social media-based educational marketing strategies. The results of the study show that since 2020 to 2024 Muhammadiyah boarding school (MBS) has implemented a social media-based educational marketing strategy as a marketing promotion media, from the implementation of social media-based marketing strategies there has been an increase in the number of students by presenting a good image to the public to convince parents of students to use educational service products offered through social media websites, Facebook, Instagram, and TikTok.